Enhancing leadership qualities through executive coaching: conceptualizing the learning process within coaching conversation in Malaysia - Nawab Zadah Khan, Nasreen Khanum; Arshad, Mohd Mursyid; Ismail, Ismi Arif; Omar, Zoharah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Despite the increasing demand for executive coaching programme, there are still a lot of scepticisms around its effectiveness and limited empirical research to support evidence of effective learning through the coaching process. Practitioners are more focused on the outcome with limited understanding on the science behind its process. The aim of this research is to conceptualise the learning process within coaching conversation to understand how the process able to enhance leadership qualities within leader. This knowledge could facilitate coaches to improve their coaching practise and making impact changes in coachees’ life. Using qualitative case study approach, data were collected through semi-structured in-depth interviews that involved nine informants from both coach and coachee that has participated in any executive coaching programme in Malaysia. Selection criteria for coach is that they have conducted executive coaching programme extensively as part of their service for more than five years and have reached to the highest level of professionalism as Professional Certified Coach (PCC) and coachees were individual that holds executive position in their organisations. Findings from the interviews revealed that coachee learnt in six different ways through the coaching process - indirect influence from coach as a role model, enhancing leader's strategic skills, providing positive leadership ecosystem; enhancing leader's cognitive ability; developing attitude as a leader; exposing leader's to effective communication; and supporting leader's emotional development. As conclusion, although coaching is understood as a simple developmental tool where powerful questioning is used as its main fundamental technique, it is not as straight forward as it seems and there are deeper and complex cognitive activities wired to support the changes and enhancement of leadership qualities within leaders. These changes are seen as the outcome of an effective coaching conversation where the process is still under explored and not fully understood.